Adjuvant Chemotherapy plus Radiation for Locally Advanced Endometrial Cancer - Matei, Daniela; Filiaci, Virginia; Randall, Marcus E; Mutch, David; Steinhoff, Margaret M; DiSilvestro, Paul A; Moxley, Katherine M; Kim, Yong M; Powell, Matthew A; O’Malley, David M; Spirtos, Nick M; Small, William; et al. (The New England journal of medicine, 2019)
After a median of nearly 4 years of follow-up, the use of radiotherapy combined with chemotherapy in patients with stage III or IVA endometrial carcinoma was not associated with longer relapse-free survival than the use of chemotherapy alone.